Significance of Gene Diagnosis in Acute Myeloid Leukemia with the Emergence of New Molecular Target Drug Treatment - Hiroki Yamaguchi (Journal of Nippon Medical School, 2022)
Acute myeloid leukemia (AML) is a heterogeneous hematopoietic malignancy accompanied by impaired differentiation and autonomous proliferation of hematopoietic stem cells. Standard induction therapy results in first complete remission among 70% of patients with AML; however, approximately half of these patients relapse and become refractory. Allogeneic hematopoietic cell transplantation is a useful treatment for relapsed and refractory cases. However, transplantation-related mortality is approximately 20%, which is not a low value, and quality of life after transplantation decreases. Therefore, there is a need to stratify the prognosis of each patient and implement this treatment appropriately. Owing to recent advances in genome analysis technology, many gene mutations involved in onset and recurrence of AML have been discovered. These abnormalities and mutations not only have clinical application as prognostic factors and minimal residual disease markers, but they may also contribute to novel molecular targeted drug development. Many new drugs such as first-generation FMS-like tyrosine kinase 3 (FLT3), isocitrate dehydrogenase 1 and 2 (IDH1/2), and B cell lymphoma 2 (BCL2) inhibitors have been developed in the West. In addition, the second-generation FLT3 inhibitors gilteritinib and quizartinib were developed in Japan, and treatment outcomes for patients with AML have improved. However, there is still a large disparity in drug availability between the West, and Japan. As a result, treatment guidelines in the West cannot be applied in the clinical setting in Japan. In this study, we assessed the molecular target drug treatment by gene diagnosis for treatment of AML patients.